Knockdown of circ-FANCA alleviates LPS-induced HK2 cell injury via targeting miR-93-5p/OXSR1 axis in septic acute kidney injury - Heyun Li; Xia Zhang; Peng Wang; Xiaoyan Zhou; Haiying Liang; Caoni Li (Diabetology & Metabolic Syndrome, 2021)
Abstract Background Sepsis is life-threatening disease with systemic inflammation and can lead to various diseases, including septic acute kidney injury (AKI). Recently, diverse circular RNAs (circRNAs) are considered to be involved in the development of this disease. In this study, we aimed to elucidate the role of circ-FANCA and the potential action mechanism in sepsis-induced AKI. Methods HK2 cells were treated with lipopolysaccharide (LPS) to establish septic AKI cell model. The expression of circ-FANCA, microRNA-93-5p (miR-93-5p) and oxidative stress responsive 1 (OXSR1) mRNA was determined by quantitative real-time polymerase chain reaction (qRT-PCR). Cell viability was assessed using cell counting kit-8 (CCK-8) assay. Cell apoptosis and cell cycle distribution were measured by flow cytometry. The inflammatory response was monitored according to the release of pro-inflammatory cytokines via enzyme-linked immunosorbent assay (ELISA). The activities of oxidative indicators were examined using the corresponding kits. Dual-luciferase reporter assay and RNA immunoprecipitation (RIP) assay were applied to validate the interaction between miR-93-5p and circ-FANCA or OXSR1. Protein analysis was conducted through western blot. Results Circ-FANCA was upregulated in septic AKI serum specimens and LPS-treated HK2 cells. Functionally, circ-FANCA knockdown facilitated cell proliferation and restrained apoptosis, inflammation and oxidative stress in LPS-triggered HK2 cells. Further mechanism analysis revealed that miR-93-5p was a target of circ-FANCA and circ-FANCA modulated LPS-induced cell damage by targeting miR-93-5p. Meanwhile, miR-93-5p overexpression repressed LPS-treated HK2 cell injury by sponging OXSR1. Furthermore, circ-FANCA regulated OXSR1 expression by sponging miR-93-5p. Besides, exosome-derived circ-FANCA was upregulated in LPS-induced HK2 cells, which was downregulated by GW4869. Conclusion Circ-FANCA knockdown attenuated LPS-induced HK2 cell injury by regulating OXSR1 expression via targeting miR-93-5p.